PCMSolver: An open‐source library for solvation modeling - Di Remigio, Roberto; Steindal, Arnfinn Hykkerud; Mozgawa, Krzysztof; Weijo, Ville; Cao, Hui; Frediani, Luca (International journal of quantum chemistry, 2019)
PCMSolver is an open‐source library for continuum electrostatic solvation. It can be combined with any quantum chemistry code and requires a minimal interface with the host program, greatly reducing programming effort. As input, PCMSolver needs only the molecular geometry to generate the cavity and the expectation value of the molecular electrostatic potential on the cavity surface. It then returns the solvent polarization back to the host program. The design is powerful and versatile: minimal loss of performance is expected, and a standard single point self‐consistent field implementation requires no more than 2 days of work. We provide a brief theoretical overview, followed by two tutorials: one aimed at quantum chemistry program developers wanting to interface their code with PCMSolver, the other aimed at contributors to the library. We finally illustrate past and ongoing work, showing the library's features, combined with several quantum chemistry programs. PCMSOLVER is an open‐source library for continuum electrostatic solvation. It can be combined with any quantum chemistry code and requires a minimal interface with the host program, greatly reducing programming effort. Communication and data movement between the two is limited to the molecular electrostatic potential and apparent surface charge. This affords a significantly streamlined interface, with minimal loss of performance. A standard single point self‐consistent field implementation requires no more than 2 days of work.